Inorganic carbon is scarce for symbionts in scleractinian corals. (3rd April 2017) - Tansik, Anna L.; Fitt, William K.; Hopkinson, Brian M.
Abstract: Ocean acidification and changing sea surface temperatures stand to affect the interactions of corals and their Symbiodinium symbionts with regard to the inorganic carbon used for photosynthesis. However, there have been few investigations on the availability of dissolved inorganic carbon (DIC) for algal symbionts in hospite. This study compared the DIC‐associated photosynthetic kinetic parameters of three Caribbean corals and their freshly isolated symbionts, as well as components of the DIC concentrating systems of both corals and symbionts. Species level differences were found in the extent of inorganic carbon saturation among the coral taxa studied. Only Orbicella faveolata was photosynthesizing at maximum rates under current seawater conditions, while Porites astreoides and Siderastrea radians were at or below half DIC saturation. O. faveolata also had significantly more external carbonic anhydrase activity, indicating that this species could produce more CO2 at the coral surface than P. astreoides or S. radians . In contrast and despite differences in Symbiodinium type, the symbionts of all the corals had a similar, very low DIC half saturation constant for photosynthesis and high levels of internal carbonic anhydrase activity, showing that they live in a carbon scarce environment and invest a great deal of energy in concentrating carbon at the site of photosynthesis. Considering the diffusional dynamics of the system and the relationship of host to symbiont kinetic parameters, the most likely cause of this scarcity is host regulation of DIC delivery to the symbionts.